Investigation of Dose Minimisation Protocol for 18F-FDG PET-CT in the Management of Lymphoma Postchemotherapy Followup - L. I. Sonoda; B. Sanghera; W. L. Wong (The Scientific World Journal)
Introduction. 18F-FDG-PET-CT plays an important role in the management of lymphoma postchemotherapy followup. Some centres perform prechemotherapy baseline CT and postchemotherapy PETCT. With a concern of radiation burden, especially in young patients, this study aimed to assess if PETCT radiation dose could be reduced. Methods. Retrospective analysis of 100 lymphoma patients was performed to record sites of disease on prechemotherapy CT and postchemotherapy PETCT. The potential reduction in radiation and time achieved with PETCT limited to sites of known disease identified on prechemotherapy CT was calculated. Results. No FDG-uptake was seen in 72 cases. FDG uptake at known disease sites was seen in 24. Of the remaining 4, one had clinically significant pathology, a rectal adenocarcinoma. PETCT did not reveal any unexpected sites of lymphoma. Limiting PETCT to sites of known disease would have saved a mean radiation dose of 4 mSv (27.3%), with a mean time of 16 minutes. Conclusion. Our study suggests that young patients may benefit from reduced radiation by limiting PETCT to sites of known disease with low risk of missing significant pathology. However, in older patients, with increased incidence of asymptomatic synchronous malignancies, whole-body PETCT is advisable unless prechemotherapy PETCT has been performed.